2010
DOI: 10.1038/hr.2010.208
|View full text |Cite
|
Sign up to set email alerts
|

Brain nitric oxide production by a proline-rich decapeptide from Bothrops jararaca venom improves baroreflex sensitivity of spontaneously hypertensive rats

Abstract: Baroreflex sensitivity is disturbed in many people with cardiovascular diseases such as hypertension. Brain deficiency of nitric oxide (NO), which is synthesized by NO synthase (NOS) in the citrulline-NO cycle (with argininosuccinate synthase (ASS) activity being the rate-limiting step), contributes to impaired baroreflex. We recently showed that a decapeptide isolated from Bothrops jararaca snake venom, denoted Bj-PRO-10c, exerts powerful and sustained antihypertensive activity. Bj-PRO-10c promoted vasodilata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…A significant decrease in mean arterial pressure (MAP) accompanied by a significant decrease in heart rate (HR) was observed for both SODa and SODb, in a similar way as recently described also for the snake BPPs [31,32,36,57,66], but with a slower and long lasting effect for SODb compared to the faster effect of SODa (data not shown). Considering that the rat SOD enzyme has a key role in regulating the BP, acting as an endogenous antioxidant [67], it would be expected that peptide fragments derived from SOD protein sequence could be biologically effective only in conditions suitable for the antioxidant system's triggering.…”
Section: Page 31 Of 54supporting
confidence: 69%
See 2 more Smart Citations
“…A significant decrease in mean arterial pressure (MAP) accompanied by a significant decrease in heart rate (HR) was observed for both SODa and SODb, in a similar way as recently described also for the snake BPPs [31,32,36,57,66], but with a slower and long lasting effect for SODb compared to the faster effect of SODa (data not shown). Considering that the rat SOD enzyme has a key role in regulating the BP, acting as an endogenous antioxidant [67], it would be expected that peptide fragments derived from SOD protein sequence could be biologically effective only in conditions suitable for the antioxidant system's triggering.…”
Section: Page 31 Of 54supporting
confidence: 69%
“…In addition, the cloning and sequencing of the BPPs precursor cDNA from Bj brain not only confirmed the co-expression of the CNP in the same precursor protein in the CNS in the same was as in the venom gland, as well as in situ hybridization studies showed the expression of BPPs/CNP precursor in snake CNS regions associated to the regulation of neuroendocrine functions [30]. In addition, we believe that the recent demonstration of the effects of snake BPPs on central BP control of rats reinforces the hypothesis of the BPPs/CNP roles as neuropeptide hormones [31][32][33].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Intracellular media were obtained following cell lysis with radioimmune precipitation assay buffer (50 mM Tris, pH 7.5, 150 mM NaCl, 1% (v/v) Nonidet P-40, 0.5% (w/v) sodium deoxycholate, 0.1% (w/v) SDS, 1 mM diethylene triamine pentaacetic acid (DTPA), and 10 mM N-ethylmaleimide) and centrifugation as previously described (25). Extra-and intracellular media of NSC were directly injected into a vessel containing a saturated solution of vanadium (III) chloride in 1 M HCl at 90°C.…”
Section: Methodsmentioning
confidence: 99%
“…Recent results indicated the targets of Bj -PRO-10c, resulting in neurotransmitter release, NO production and alteration of baroreflex control, resulting in alteration of arterial pressure and heart rate [18], [19].…”
Section: Introductionmentioning
confidence: 99%